Evaluation of green roof performances for urban stormwater quantity and quality controls - Kok K.H.; Mohd Sidek L.; Chow M.F.; Zainal Abidin M.R.; Basri H.; Hayder G. (Taylor and Francis Ltd., 2023)
peak discharge; performance assessment; quality control; runoff; stormwater; tropical region; urbanization; water quality; Malaysia